Remarkable lives: Charlotte Wall in conversation with Jerome Carson. Issue 4 (24th June 2020) - Wall, Charlotte Louise; Carson, Jerome
Abstract : Purpose: The purpose of this paper is to provide a profile of Charlotte Wall. Design/methodology/approach: In this case study, Charlotte provides a short account of her background and is then interviewed by Jerome. Findings: Charlotte took comfort in being given a diagnosis of bipolar; it helped explain a lot of her problems. Research limitations/implications: It is easier to identify with a single case study and person's story than anonymised group research data. Each have their place in helping us understand mental health problems. Practical implications: Transitions are not always bad. Charlotte talks about how her life changed for the better when she went to sixth form college. The onward transition to university has also been a positive experience for her. This needs to be remembered. Social implications: As everyone is currently living through the Covid-19 pandemic, Charlotte's perspective on the importance of social support for mental well-being is critical. Thankfully, she has loving parents and a partner. There are others less fortunate. Originality/value: Charlotte shows us how she embraced her diagnosis of bipolar and her "weirdness".